8 funding opportunities for social innovators - Balamatsias, Grigorios (Social Innovation Academy, 2018)
Funding opportunities for social innovators are endless. If you have a good idea or initiative already, money can follow if you know where to look for.
Keywords: Europe

8 funding opportunities for social innovators - Balamatsias, Grigorios (Social Innovation Academy, 2018)
Funding opportunities for social innovators are endless. If you have a good idea or initiative already, money can follow if you know where to look for.
Keywords: Europe